2013
DOI: 10.1371/journal.pone.0066987
|View full text |Cite
|
Sign up to set email alerts
|

New Aspects of an Old Drug – Diclofenac Targets MYC and Glucose Metabolism in Tumor Cells

Abstract: Non-steroidal anti-inflammatory drugs such as diclofenac exhibit potent anticancer effects. Up to now these effects were mainly attributed to its classical role as COX-inhibitor. Here we show novel COX-independent effects of diclofenac. Diclofenac significantly diminished MYC expression and modulated glucose metabolism resulting in impaired melanoma, leukemia, and carcinoma cell line proliferation in vitro and reduced melanoma growth in vivo. In contrast, the non-selective COX inhibitor aspirin and the COX-2 s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
83
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(96 citation statements)
references
References 61 publications
6
83
0
3
Order By: Relevance
“…19 Despite the demonstrated tumor-promoting effects ( Figure 1A), shifts of cellular energetics away from oxidative phosphorylation could increase the CLL cells' reliance on glucose and thereby render them more susceptible toward perturbations within their glycolytic framework. 20 In fact, treating CLL cells with 2-deoxy-D-glucose and diclofenac 21 that both target glucose metabolism revealed an increased sensitivity upon stromal contact ( Figure 1K).…”
Section: Resultsmentioning
confidence: 97%
“…19 Despite the demonstrated tumor-promoting effects ( Figure 1A), shifts of cellular energetics away from oxidative phosphorylation could increase the CLL cells' reliance on glucose and thereby render them more susceptible toward perturbations within their glycolytic framework. 20 In fact, treating CLL cells with 2-deoxy-D-glucose and diclofenac 21 that both target glucose metabolism revealed an increased sensitivity upon stromal contact ( Figure 1K).…”
Section: Resultsmentioning
confidence: 97%
“…Interestingly, a study using, diclofenac, a nonsteroidal anti-inflammatory drug, showed suppression of c-MYC. This down-regulation of c-MYC that resulted in significantly reduced levels of GLUT1, LDH-α, MCT1 and coincident decrease in glucose import and lactate secretion by human melanoma cells in vitro, validating the importance of targeting this transcription factor for anti-cancer therapy [327329]. The most current, ongoing clinical trials targeting various aspects of metabolism in cancer cells are listed in Table 1.…”
Section: Current Therapeutic Options In Targeting Tumor Metabolismmentioning
confidence: 81%
“…На первичных культурах рака яичников челове-ка in vitro эти НПВС вызывали арест клеточного цикла и апоптоз опухолевых клеток [15]. Диклофенак тормозил рост меланомы in vivo у мышей и клеточной линии мела-номы in vitro [16].…”
Section: Abstract: Nonsteroidal Anti-inflammatory Drugs Cyclooxygenaunclassified
“…НПВС in vitro блокируют его, что приводит к снижению экс-прессии генов-мишеней β-катенина-циклина D 1 , cМyc и Axin2 и стимуляции NF-kB сигнального пути, что было показано на культуре клеток как колоректального рака [17], так и глиобластомы [13], и меланомы [16].…”
Section: Abstract: Nonsteroidal Anti-inflammatory Drugs Cyclooxygenaunclassified
See 1 more Smart Citation